Shared services and outsourcing : a contemporary outlook : 10th Global Sourcing Workshop 2016, Val d'Isère, France, February 16-19, 2016, Revised selected papers /: a contemporary outlook : 10th Global Sourcing Workshop 2016, Val d'Isère, France, February 16-19, 2016, Revised selected papers. (2016) - Unknown
No abstract available